2012
DOI: 10.14712/23362936.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Arterial Embolization of Symptomatic Giant Hemangioma of the Liver

Abstract: The cavernous hemangiomas of the liver are usually small sized and asymptomatic. Most of them are incidentally diagnosed and a very small portion requires therapy. Giant hemangioma can be symptomatic, and this condition is the indication for treatment. The striking complication of surgical treatment of cavernous hemangiomas is intra-operative bleeding. In this case, we aimed to demonstrate that the risk of intraoperative bleeding can be eliminated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Furthermore, there was only mild blood loss for a hemangioma of this size. Our outcomes are consistent with those from Vassiou et al, Bailey et al, and Kayan et al, who performed a similar technique with minimal blood loss, improved mobilization, and without inflow vascular occlusion [19][20][21]. Our quantified blood loss was also similar to the 400 mL reported by Zhou et al, who also reported a much longer post-operative stay than our patient (16 days vs. 7 days) [23].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, there was only mild blood loss for a hemangioma of this size. Our outcomes are consistent with those from Vassiou et al, Bailey et al, and Kayan et al, who performed a similar technique with minimal blood loss, improved mobilization, and without inflow vascular occlusion [19][20][21]. Our quantified blood loss was also similar to the 400 mL reported by Zhou et al, who also reported a much longer post-operative stay than our patient (16 days vs. 7 days) [23].…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, surgical resection remains an attractive option if the hemangioma is deeply located in the liver parenchyma, occupies an entire lobe, or does not have a free surface from Glisson's capsule [13]. Trans-arterial embolization has been proposed as a treatment option in giant symptomatic hemangiomas, both alone and in combination with resection [15][16][17][18][19][20][21][22]. In a study of 98 patients with a hemangioma > 5cm, TAE monotherapy resulted in resolution of pain and distension in 87% of patients with baseline symptoms, with partial reduction in the other 13% [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, embolization of hepatic hemangiomas is currently not considered a definitive treatment. However, there were reports that arterial embolization for large hemangiomas which were performed prior to surgical resection facilitated mobilization of the liver by shrinking the hemangioma and, consequently, decreased intraoperative hemorrhage (24)(25)(26)(27)(28)(29). Considering the various complications and vascular recanalization after embolization which might delay the operation and result in the loss of an opportunity for radical resection, some authors recommend urgent operation after embolization (26).…”
Section: Discussionmentioning
confidence: 99%